A Practical Guide to Skin Cancer (Springer International Publishing, 2018)
Skin cancer is the most common malignant neoplasm, and with the increasing regularity of such tumors comes the need for a practical guide for medical professionals to reference for diagnosis, management, and treatment. This book covers everything from the epidemiology of the skin cancer, clinical presentation with clinical photographs, diagrams of the most common anatomical locations, to histological descriptions, special stains/tests for diagnosis, and a treatment algorithm in chart form. A Practical Guide to Skin Cancer offers brief and succinct chapters with pertinent references, as well as high quality color photographs, diagrams, tables, and charts. Written for dermatologists, dermatology residents, and oncologists, this book allows for the reader to quickly and easily obtain the information regarding a tumor's clinical presentation, patient evaluation and treatment algorithms, proving essential for every physician who encounters these tumors in their daily practice.